2016
DOI: 10.1590/0037-8682-0026-2016
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of hantavirus infection in an urban area in Mato Grosso State, Brazil

Abstract: Introduction:In Brazil, Mato Grosso (MT) has the highest number of hantavirus cardiopulmonary syndrome cases. Our study aimed to identify anti-hantavirus antibodies in the sera of patients from Sinop, MT, presenting with acute febrile illness. Methods: A retrospective analysis of data for 198 sera samples assessed using enzyme-linked immunosorbent assay (ELISA) was conducted. Results: Immunoglobulins G (IgGs) against the hantavirus nucleoprotein were found in 13.6% of the tested sera. No sample had immunoglobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…Sex bias does occur in infectious disease epidemiology including orthohantavirus infections [ 24 , 27 ]. In Barbados, females were more likely to be infected with orthohantavirus than males and this agrees with studies in the Netherlands and Brazil [ 56 , 57 ]. More research is needed to provide more insight into this gender disparity with respect to orthohantavirus infection in Barbados and possibly the Caribbean.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sex bias does occur in infectious disease epidemiology including orthohantavirus infections [ 24 , 27 ]. In Barbados, females were more likely to be infected with orthohantavirus than males and this agrees with studies in the Netherlands and Brazil [ 56 , 57 ]. More research is needed to provide more insight into this gender disparity with respect to orthohantavirus infection in Barbados and possibly the Caribbean.…”
Section: Discussionsupporting
confidence: 89%
“…This appears to influence orthohantavirus infection in Barbados with higher infection rates observed in patients from urban rather than rural areas [64,65]. This was also observed in Brazil, where females were more likely to become infected and occupation (housewives) was identified as a possible risk [57]. However some research has shown rural areas with a higher risk of orthohantavirus infection than urban areas [65].…”
Section: Influence Of Seasonality and Geographic Locationmentioning
confidence: 86%
“…In addition, four of the seropositive patients attested to having never worked outside of this state, suggesting that these infections occurred within the state's geographic boundaries. The IgG prevalence in this study was lower than that of other regions in Brazil where HCPS is highly endemic, such as 13.6% in the State of Mato Grosso 11 . However, an IgG prevalence of 2% was reported in Uberlandia City in Minas Gerais State 12 , which is another hantavirus-endemic region; this is similar to the prevalence found in the present study.…”
contrasting
confidence: 78%
“…Recently, in the study conducted by Vieira et al 13 , high anti-hantavirus IgG seroprevalence of 13.6% was shown in the City of Sinop in the Mato Grosso State. The study site may justify this in part because the state has the second highest number of HCPS cases nationwide.…”
mentioning
confidence: 95%
“…Residents of urban areas also have links to the field, through work or field-related activities which might increase the risk of exposure to rodent reservoirs 11,13 . Thus, when the questionnaire was administered, a majority of the population expressed having experienced situations considered to enhance the risk for hantavirus infection, including rural tourism (74%) and exposure to house cleaning in the countryside, sheds, and other similarities (71%).…”
mentioning
confidence: 99%